Theology for ministry : how doctrine affects pastoral life and practice - Edwards, William R. (William Rob); Ferguson, John C. A.; Van Dixhoorn, Chad B. (Phillipsburg, New Jersey : P&R Publishing Company, 2022)
"Deeply connecting theology with practice, this book encourages rich biblical-theological reflection for growing and sustaining a vibrant ministry-applying more than twenty key Christian doctrines to pastoral work"--
Scripture : foundational for life and ministry / R. Carlton Wynne -- The trinity : the doctrine of God and the pulpit / Robert Letham -- The decrees of God : what every pastor must know / Douglas Kelly -- Creation : the essential setting for proclaiming Christ / Ian Hamilton -- Providence : confidence in God's purpose to perfect his people / Michael McClenahan -- Humanity : the need of theological anthropology for everyday ministry / John McClean -- Covenant : the structure of reformed theology and environment of reformed piety / David B. McWilliams -- The person of Christ : the deeper protestant conception and the church's heavenly-mindedness / Lane G. Tipton -- The work of Christ : remembering the forgetfulness of God in pastoral ministry / David Gibson -- Union with Christ : gospel ministry as dying and rising with Jesus / Philip Graham Ryken -- The holy spirit : new creation power for God's redeemed people / Dennis E. Johnson -- Faith and repentance : implications for the gospel call in preaching / Cornelis P. Venema -- Justification : the declaration of righteousness that shapes our present ministry / John C. A. Ferguson -- Sanctification : a pastor's labor for the obedience of faith / William R. Edwards -- Adoption / Ligon Duncan -- Perseverance : the hope-full gospel that encourages abiding faith / Paul D. Wolfe -- Assurance of faith : pastoral wisdom for struggling Christians / Joel R. Beeke -- Christian liberty : the pastor as the guardian of freedom / David Strain -- The law of God : preaching the law as competent ministers of a new covenant / Philip S. Ross -- Communion of the saints : sharing the spirit-endowed riches of Christ's gifts and graces / A. Craig Troxel -- The church : the well-ordered church in a world of distrust / Mark A. Garcia -- Worship : grounding our practice in God's word / W. Robert Godfrey -- The sacraments : communion with God in union with Christ / Chad Van Dixhoorn -- Missions : the magnetic person of Jesus Christ / Daniel Strange -- Eschatology : how the telos of humanity must inform pastoral ministry / Michael Horton -- Sinclair B. Ferguson : teacher, pastor, preacher, author / Chad Van Dixhoorn -- Afterword: Theological reflections on the true nature of friendship / William Edgar.
Includes bibliographical references and indexes.
Keywords: Pastoral theology; Church work; Theological anthropology